Presenting a Model for Parental Sexual Upbringing of Children: A Grounded Theory Study - Parsayan, Mohammadreza; Jabalameli, Sheida; Aghahoseini, Taghi; Khoshakhlagh, Hassan (Psychology of Woman Journal, 2024)
Objective: The purpose of this research is to present a model for the sexual upbringing of children by parents, utilizing a practical qualitative approach with the grounded theory method. Methods and Materials: The research population included informed parents (20 mixed-gender individuals) with children aged 8-12 years, holding at least a high school diploma, and professors (15 individuals) from universities in Isfahan. Participants were selected based on theoretical and purposive sampling. Data collection continued with in-depth interviews guided by questions until theoretical saturation was achieved. The data analysis process was performed through multiple stages of coding. Findings: The findings indicate that causal conditions (misconceptions about sexual education and upbringing based on individual values), contextual conditions (social norms, acceptance of the issue of sexual education), intervening conditions (attention to the psychological needs of the child, sense of responsibility towards the child, and consideration of children’s psychological states), strategies (adherence to the law, parental blame, and a scientific approach to sexual education), and outcomes (institutionalization of a specific sexual pattern) were identified as different stages of the paradigmatic model of sexual education. Conclusion: The sexual education in each country and its curriculum are based on the cultural teachings and beliefs of that country. Therefore, the proposed model of this research aids in addressing the necessity and need for education on the cultural-social structures prevailing in the Iranian society.